If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14z-18=12z+5(13z+9)
We move all terms to the left:
14z-18-(12z+5(13z+9))=0
We calculate terms in parentheses: -(12z+5(13z+9)), so:We get rid of parentheses
12z+5(13z+9)
We multiply parentheses
12z+65z+45
We add all the numbers together, and all the variables
77z+45
Back to the equation:
-(77z+45)
14z-77z-45-18=0
We add all the numbers together, and all the variables
-63z-63=0
We move all terms containing z to the left, all other terms to the right
-63z=63
z=63/-63
z=-1
| 2.5=3x-1 | | 2x+4=94 | | 2b-5=b+1 | | 3(y-5)=7y | | 42=-7(d-7-14 | | 94=3b+13 | | -7x-x=10+2-7x-5 | | 7(4+1/7x)=8(7) | | -6y+9=-6y-6 | | x^2=22x=-21 | | -2.5=17.1=y/6 | | x=5/3x+8 | | 7+5c=3 | | -4x+12=3x+-8 | | 2+(4/5)b=(9/10)b | | 14x+13x-8=19 | | -2(-18-6b)=-6(6b+10) | | 8x−2=−97x | | 4-(-8x+3)=-12-32x | | 3(y-5)=y=7 | | 3x+8=x+42 | | 2x4=94 | | 6x10=4x+40 | | -3(x-4)-4=2(-x-16) | | 3(8+3x)=3x-(-8x-6) | | 2x+3+151=180 | | 15x-20=-19x+7 | | 0.5j-(-8.5)=18 | | -2(12-18n)=6(-6+4n) | | 5x-2+3+4+90=180 | | -2x-1-x=-19-x+2 | | -6q=3-5q |